DARC: A Distributed and Adaptive Routing Protocol in Cluster-Based Wireless Sensor Networks - Zhezhuang Xu; Liquan Chen; Lianyang Cao; Ting Liu; Dong Yang; Cailian Chen (International Journal of Distributed Sensor Networks)
Due to the limited energy of wireless sensor nodes, the energy efficiency of data collection is a key issue in wireless sensor network (WSN). Dynamic clustering is a scalable and energy efficient solution for data collection in WSN. However, it suffers from the imbalanced energy consumption in the intercluster communication. To solve this problem, in this paper, we propose a distributed and adaptive routing protocol for cluster-based wireless sensor networks (DARC). In DARC, an adaptive energy threshold is proposed for the cluster head to control its intercluster routing mode, and a tunable cost function is designed for relay selection. Simulation results prove that DARC effectively balances the energy consumption in the intercluster communication and hence improves the energy efficiency and prolongs the network lifetime.